2015
DOI: 10.5370/jeet.2015.10.4.1780
|View full text |Cite
|
Sign up to set email alerts
|

A Study on a Gain-Enhanced Antenna for Energy Harvesting using Adaptive Particle Swarm Optimization

Abstract: -In this paper, the adaptive particle swarm optimization (APSO) algorithm is employed to design a gain-enhanced antenna with a reflector for energy harvesting. We placed the reflector below the main radiating element. Its back-radiated field is reflected and added to the forward radiated field, which could increase the antenna gain. We adopt the adaptive particle swarm optimization (APSO) algorithm, which improves the speed of convergence with a high frequency solver. The result shows that performance of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In ambient energy harvesting scenario, the incoming signal may come from multiple frequencies with an unknown angle of incidence. Thus, a rectenna with circular polarized antenna is advantageous as it can supply a nearly constant output direct current (DC) voltage irrespective to the orientation of the antenna …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ambient energy harvesting scenario, the incoming signal may come from multiple frequencies with an unknown angle of incidence. Thus, a rectenna with circular polarized antenna is advantageous as it can supply a nearly constant output direct current (DC) voltage irrespective to the orientation of the antenna …”
Section: Introductionmentioning
confidence: 99%
“…However, the gain produced in these proposed structure are comparatively low, which makes them incompatible for ambient energy harvesting. For efficient energy harvesting, a low profile with wideband CP and high‐gain antenna is desirable. In energy harvesting research, CP antenna with 23% AR bandwidth is suggested in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Kang reported a convenient synthetic procedure. He has improved a reflector by using the particle swarm optimization (PSO) 98 | P a g e www.ijacsa.thesai.org algorithm [5]. The reflector and ring slot antenna works to enhance the gain.…”
Section: Gain-enhanced Antenna With Reflectormentioning
confidence: 99%
“…Therefore, it is costly to recharge the power. In this case, it is required to keep the sensors working for a longer time by harvesting the energy [5]. In that situation, the energy harvesting will increase the default lifetime for different wireless applications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high search efficiency, PSO has been widely used in enhancing antenna gain [19] and beam pattern synthesis [20] and improving BCE of a MPT system [10]. In this work, the synthesis of the sparse uniform-amplitude transmitting array is discussed for the optimal MPT.…”
Section: Introductionmentioning
confidence: 99%